VD_FINDINFO Jug / 2018 / 374 vom 29. März 2018 - VD Tribunal cantonal (2018)
CONSTATATION DES FAITS, PRÉSOMPTION D'INNOCENCE, VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION, FIXATION DE LA PEINE | 219 CP, 47 CP, 10 CPP (CH)